Manajemen Risiko dalam Transaksi Perdagangan Valuta Asing - Devy Sofyanty; Vera Agustina Yanti; Danny Ong; Suwantica Suwantica (Universitas Batanghari Jambi, 2022)
Foreign exchange trading carries a high level of risk, so risk management is essential. This study aims to determine the risk of foreign exchange trading and to determine the application of risk management in foreign exchange trading. The research was conducted at PT Monex Investindo Futures Jakarta. The research method used a qualitative descriptive method. Based on the results of the study, it was found that the risk in forex trading is the risk of unexpected changes that cause market conditions to reverse direction, this can be due to economic or political events that affect market movements. The analysis used to determine the volatility of the foreign exchange market is to use technical and fundamental analysis. Fundamental analysis is based on data from economic and political news, while technical analysis is carried out using charts and indicators. There are five risk management implemented at PT Monex Investindo Futures to minimize losses resulting from price movements on the foreign exchange market, namely: moving average, bollinger band, parabolic SAR, Average Directional Movement Index and Robotics